The Influence of Using Tiktok Social Media Towards Students' Learning Outcomes In Thematic Learning At Grade III of SD Negeri 01 Ulak Karang Selatan - Lesma wati; Nofriza Efendi; Yona Syaida Oktira; Ayunis Ayunis (The Future of Education Journal, 2024)
This research aims to determine whether there is an influence of the use of TikTok social media on student learning outcomes in thematic learning in Class III of SD Negeri 01 Ulak Karang Selatan. This research was based on several students who were influenced by TikTok social media, for example when their friends asked other friends questions such as: asking for assignments with the words "Is your assignment ready?", and the friends who answered gave the answers they saw from videos provided by the TikTok application and the researcher saw that after the break, several students only discussed the TikTok video they saw last night, not discussing what lessons they had previously learned or what grades they had gotten. Therefore, this research aims to find out whether there is an influence of the use of TikTok social media on student learning outcomes in thematic learning in class III of SD Negeri 01 Ulak Karang Selatan. This research is quantitative with a pre-experimental designs (nondisegns) approach and then tools for collecting data using observation, questionnaires, student learning results tests and documentation. The sample for this research is class III students at SD Negeri 01 Ulak Karang Selatan. Based on the research results obtained, it can be seen that the t-count is 7.797 and the t-table is 2.063, so it can be concluded that 7.797 > 2.063 and a significant value of 0.000 < 0.05 is obtained. So it can be concluded that Ha is accepted, H0 is rejected. So the social media variable partially influences learning outcomes.